1989
DOI: 10.7326/0003-4819-110-12-970
|View full text |Cite
|
Sign up to set email alerts
|

Unique Alterations of Thyroid Hormone Indices in the Acquired Immunodeficiency Syndrome (AIDS)

Abstract: Infection with HIV produces unique alterations in thyroid function. A progressive decline in rT3 and elevation in thyroxine-binding globulin accompany advancing HIV infection. The persistence of a normal T3 despite progression of HIV infection may contribute to weight loss. A low serum T3 on admission correlates with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
6

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(47 citation statements)
references
References 21 publications
1
39
1
6
Order By: Relevance
“…Euthyroid sick syndrome is characterized by normal or low FT 4 levels, low T 3 levels, elevated reverse T 3 (rT 3 ) levels and low or normal TSH levels (31). This is a physiological adaptive phenomenon of the body to conserve energy during periods of extreme stress and during an infection.…”
Section: Introductionmentioning
confidence: 99%
“…Euthyroid sick syndrome is characterized by normal or low FT 4 levels, low T 3 levels, elevated reverse T 3 (rT 3 ) levels and low or normal TSH levels (31). This is a physiological adaptive phenomenon of the body to conserve energy during periods of extreme stress and during an infection.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone (T 3 ) and its receptors (TRs) have been suggested to play a role in HIV development. First, AIDS or ARC patients have multiple endocrine abnormalities and their serum T3 levels are often altered [3], [4]. Low levels of T3 often correlate with survival rate, and in all levels of illness, there is an increase in T3-binding globulin levels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been also suggested a role for the T3 in HIV-1 LTR regulation, revealing the existence of binding sites for the T3 receptor (T3R) in different regions of the LTR sequence (Sawaya et al 1996, Xu et al 1996, Recio et al 2000, Hsia & Shi 2002. In this sense, previous studies have revealed that different hormones, such as T3, may have a role in AIDS development (LoPresti et al 1989), and a therapeutic use of retinoic antagonists has been already proposed to repress viral replication by inhibiting retinoid-dependent transcription (Lee et al 1994, Hanley et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the genetic predisposition of the host and the virus is the most important determinant for prediction and understanding the course of HIV infection and progression to AIDS. At this respect, previous studies have revealed that ligands of nuclear receptors such as thyroid hormones (T3) may have a role in AIDS development (LoPresti et al 1989). In fact, data from our laboratory, among others, have demonstrated a role for T3 and retinoic acid (RA), other nuclear receptor ligands, on HIV-1 LTR regulation, demonstrating the binding of RA receptors (RARs) and T3 receptors (TRs) to different LTR regions (Desai-Yajnik & Samuels 1993, Sawaya et al 1996, Xu et al 1996, Recio et al 2000, Hsia & Shi 2002.…”
Section: Introductionmentioning
confidence: 99%